Responses of Persian walnut on foliar applications of different biostimulants - Simon, Gergely; Bujdosó, Géza; Cvetkovic, Miljan; Tevfik Alp, Ozan; Kithi, Laurine; Oláh, Richárd; Ficzek, Gitta; Végvári, György (Frontiers in Plant Science, 2023)
Biostimulants have different effects on plants. The aim of this paper is to determine responses of the 'Alsószentiváni 117' walnut cultivar on foliar applications of different biostimulants (Wuxal Ascofol, Kondisol, Alga K Plus). The nut traits (nut length, nut diameter, nut weight, kernel weight) and some phenolic compounds of the kernel were measured and detected. In 2020, during warmer early spring weather conditions under pistillate flowering receptivity, chlorogenic acid and quercetin content of kernels treated with Kondisol were higher than in control. All biostimulants influenced positive effects on catechin and rutin content, as well as treatments made with Wuxal Ascofol and Kondisol increased the juglon content of the kernel. In 2021, when the spring weather was typical for that period, only the Kondisol treatments had increasing effects on the catechin and chlorogenic acid content, than the control. The rutin and quercetin concentrations reached the highest value in this trial by Alga K Plus applications. The juglon content decreased in this year compared to the control. The pirocathecin, cinnamic acid, and gallic acid (except Wuxal Ascofol treatment in 2021) content 2 decreased in all treatments in both observed years. Responses of woody fruit species on biostimulants applications depend on the weather conditions. Biostimulants had positive effects on the nut size characteristics in both observed years.